SOCIAL MEDICINE APPROACH IN RESOLUTION OF THE PROBLEM OF CONTAMINATIONOF PUBLIC AREASWITH DOG FECES AND ITS PUBLIC HEALTH RELEVANCE - Ristić, Marko; Jovanović, Nemanja M.; Ilić, Tamara (Acta medicae Medianae, 2023)
Since dogs and humans share their living environments and effectuatevery close contactswith each other, with dog owners not caring adequately for their pets, there is a possibility of transmission of particular parasitic diseases from dogs to humans. In view of the fact that dogs are carriers and definitive hosts of a large number ofzoonotic endoparasites, their feces may represent a source of infection for humans and a real threat to their health. That is the reason for raising the level of awareness among citizens about the necessity of executing zoohygienic measures in dog breeding, as well as about the significance of causally planned dehelminthization and anti-ectoparasitic treatments. Further, it is essential that dog owners perform regular coprological examinations, immediately after getting the dog and four times a year afterwards, abiding by the principle of shifting the preparations used based on their different chemical formulations. A timely diagnosis of intestinal parasites in dogs and proper treatment of infected animals enable the prevention of these infections in humans. Contamination of public areas with intestinal parasites from dog feces represents a public health problem that should be kept under control using the appropriate social medicine approach. Such an approach would typically involve health education measures related to the control of parasite transmission in the environment, provision ofthe guidelines to dog owners for prevention of the occurrence, persistence, and spread of zoonotic diseases, and health education of medical and veterinary professionals, pet owners, and the wider community regarding the preservation of the health of both humans and pet animals. An increased level of knowledge and corrected attitudes and behaviors among individuals would certainly contribute to more effective prevention of zoonotic diseases.
Keywords: dog, intestinal parasites, diagnosis, prevention, zoonotic diseases